Comparative efficacy and safety of multiple acupuncture therapies for post stroke cognitive impairment: a network meta-analysis of randomized controlled trials - Liu, Yang; Zhao, Lu; Chen, Fuyan; Li, Xingping; Han, Jiangqin; Sun, Xiaowei; Bian, Mingtong (Frontiers in Neurology, 2023)
Objective: We aimed to compare and evaluate the efficacy and safety of different acupuncture-related therapies for PSCI in an attempt to identify the best acupuncture therapies.We searched eight databases including PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trials, CBM, VIP, CNKI , and Wan fang database to find randomized controlled trials (RCTs) of acupuncture-related therapies for PSCI from the inception of the database to January 2023. Two researchers independently assessed the risk of bias in the included studies and extracted the study data. Pairwise meta-analyses for direct comparisons were performed using Rev Man 5.4 software. Bayesian network meta-analysis (NMA) was performed using STATA 17.0 and R4.2.4 software. The quality of evidence from the included studies was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system. Adverse effects (AEs) associated with acupuncture therapy were collected by reading the full text of the included studies to assess the safety of acupuncture therapy.Results: A total of 62 RCTs involving 5073 participants were included in this study. In the paired meta-analysis, most acupuncture-related therapies had a positive effect on cognitive function and self-care of daily living in patients with PSCI compared with cognitive training. Bayesian NMA results suggested that ophthalmic acupuncture plus cognitive training was the best acupuncture therapy for improving MMSE scores, with scalp acupuncture plus cognitive training ranking as the second. The MoCA results suggested that warm acupuncture plus cognitive training was the best acupuncture therapy. In terms of improvement in daily living self-care, scalp acupuncture plus body acupuncture was the best acupuncture therapy for improving MBI scores. The most common minor AEs included subcutaneous hematoma, dizziness, sleepiness, and pallor.According to our Bayesian NMA results, OA+CT and WA+CT were the most effective acupuncture treatments for improving cognitive function, while SA+BA was the best acupuncture treatment for improving the performance of self-care in daily life in patients with PSCI. No serious adverse effects were found in the included studies, and acupuncture treatment appears to be safe and reliable. However, due to the low methodological quality of the included studies, our findings need to be treated with caution.